The Influence of Entamoeba histolytica Against Some Gut Microbiota in Children with Acute Amoebic - AlSalim, Hutaf A. A.; Hassen, Rafeef F. (Iraqi Journal of Science, 2023)
This study aimed to evaluate the relationship between the microbiota number of some common bacterial species in children's gut with Entamoeba histolytica infection. To achieve that,49 samples of stool were collected, 29 from children with acute amebiasis and 20 from healthy children, children's ages ranging from 1 month to 12 years from both genders. Counting three types of bacteria Lactobacillus spp., Bifidobacterium spp. and Escherichia coli, using the standard curve obtained from Real-Time PCR was accomplished. The standard curve was made from decimal serial dilution of samples containing an unknown number of bacteria. The results showed that E. histolytica infection creates considerable changes in the intestinal microbiota numbers. Lactobacillus spp., Escherichia coli and Bifidobacterium spp. numbers were affected. The mean values of Lactobacillus spp. and Escherichia coli in the patient's group (children with amebiasis) were increased compared to the control group (healthy children). The mean value in the patient groups were (1947.4) and (430657.9), while in the control groups were (1400.16) and (193927.7) for Lactobacillus spp. and Escherichia coli, respectively. Whereas the mean value of Bifidobacterium spp. showed a significant decrease in the patient group (103.875) compared with the control group (166.75). In conclusion, this study show alteration in predominant gut bacteria in E. histolytica infected children.